PEMIMPIN DALAM PENDIDIKAN AL-QURAN DAN HADITS - Pratiwi, Sekar; Syafruddin, Syafruddin; Rehani, Rehani (Universitas Dharmawangsa, 2024)
Leaders in Islam have a very important role in guiding, protecting and managing the affairs of the people and society. Leadership in Islam includes an understanding of the role, characteristics and responsibilities of a leader according to Islamic teachings. In Islam, leaders are considered role models who can be mentors, directors and educators for their community. This research uses Systematic Literature Review (SLR), a research method that summarizes primary research results to present more comprehensive and balanced facts